PEMANFAATAN ALGA BILANGAN DAN MR. X DENGAN STRATEGI THE POWER OF TWO DALAM PEMBELAJARAN PROSES PEWARISAN SIFAT UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS IX5 SMP NEGERI 1 WAWO - Eddy Ilhamsyah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2015)
This research is a Classroom Action Research which takes place in 2 cycles with the aim to find out whether the use of Number Algae and Mr. X with the Strategy of The Power of Two can increase motivation and learning outcomes of class IX5 students of SMP Negeri 1 Wawo. Data were collected by pre-test post-test instruments, student activity observation sheets, teacher teaching ability assessment instruments, and guidelines for interviewing student opinions on learning the concept of inheritance. Quantitative data processing results from post-test cycle I and cycle II with the format of daily test results analysis. Descriptive analysis is presented in the form of a statistical table, while for qualitative data the results of observations are by giving a score (value) to the aspects assessed or to alternative answers. The results of the post-test data analysis, in the first cycle the number of students completed 25 students (65.79%) and the unfinished 13 students (34.21%) with an average value of 69.61. In the second cycle, the number of students completed 32 students (84.21%) and 6 students (15.79%) with an incomplete score of 78.68. This means that it has exceeded the minimum completeness criteria (KKM) that have been set for the basic competency concept of inheritance namely 70% with an average value of 75.00. The results of the data analysis of student activeness in learning the inheritance process using Number Algae and Mr. X with The Power of Two Strategy in cycle I of 38 students, 4 students (10.53%) showed a less active activity scale, 5 students (13.15%) were quite active, 17 students (44.73%) were active and 12 students (31.59%) were very active with an average activeness of 3.18. In the second cycle, of 38 students, only 6 students (15.79%) showed quite active activeness scale, 15 students (39.47%) were active, and 17 students (44.74%) were very active with average student activity 3.34. Based on the results of the data analysis above, it can be concluded that the Algae Numbers and Mr. X with the Strategy of The Power of Two can increase motivation and learning outcomes of students of class IX5 Wawo 1 Public Middle School in learning the process of inheritance.